PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR JAKARTA ISLAMIC INDEX YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdullah Abdullah (AkMen JURNAL ILMIAH, 2019)
ABDULLAH, 2019. Effect of Financial Performance on Stock Prices on the Jakarta Islamic Index Sector Companies listed on the Indonesia Stock Exchange in 2016-2019. This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Return On Equity, and Working Capital Turnover partially, as well as simultaneously on the Stock Prices of the Jakarta Islamic Index Sector Companies listed on the Indonesia Stock Exchange in 2016-2019. The population in this study is the Jakarta Islamic Index Sector Companies listed on the Indonesian stock exchange as many as 30 companies. The sample of this study was 10 (ten) companies selected based on criteria, namely: Jakarta Islamic Index Sector Companies listed on the Indonesia Stock Exchange Period 2016-2019; Publish audited financial statements; Having profit; and have distributed cash dividends during the observation period. The results of this study indicate that the Current Ratio (X1) Debt to Equity Ratio (X2) and Working Capital Turnover (X4) partially have no significant effect. Whereas Return On Equity (X3) has a positive and significant effect on stock prices on the Jakarta Islamic Index Sector Companies listed on the Indonesia Stock Exchange Period 2016-2019. Simultaneously Current Ratio (X1), Debt to Equity Ratio (X2), Return On Equity (X3), and Working Capital Turnover (X4) have a positive and significant effect on the Share Prices of Jakarta Islamic Index Companies in the Indonesia Stock Exchange Period 2016-2019. The dominant influential variable is Return On Equity (X3). ABDULLAH, 2019. Pengaruh Kinerja Keuangan Terhadap Harga Saham pada Perusahaan Sektor Jakarta Islamic Index yang terdaftar di Bursa Efek Indonesia Tahun 2016-2019. Penelitian ini bertujuan untuk mengetahui pengaruh Current Ratio, Debt to Equity Ratio, Return On Equity, dan Working Capital Turnover secara parsial, maupun simultan terhadap Harga Saham pada Perusahaan Sektor Jakarta Islamic Index yang terdaftar di Bursa Efek Indonesia Tahun 2016-2019. Populasi dalam penelitian ini adalah Perusahaan Sektor Jakarta Islamic Index yang terdaftar di bursa efek Indonesia sebanyak 30 perusahaan. Sampel penelitian ini adalah 10 (sepuluh) perusahaan yang dipilih berdasarkan criteria yaitu: Perusahaan Sektor Jakarta Islamic Index yang terdaftar di Bursa Efek Indonesia Periode 2016-2019; Menerbitkan laporan keuangan yang telah diaudit; Memiliki keuntungan (profit); dan pernah membagikan Cash Deviden selama periode pengamatan. Hasil penelitian ini menunjukkan bahwa Current Ratio (X1) Debt to Equity Ratio (X2) dan Working Capital Turnover (X4) secara parsial tidak berpengaruh signifikan. Sedangkan Return On Equity (X3) berpengaruh positif dan signifikan terhadap harga saham pada Perusahaan Sektor Jakarta Islamic Index yang terdaftar di Bursa Efek Indonesia Periode 2016-2019. Secara Simultan Current Ratio (X1), Debt to Equity Ratio (X2), Return On Equity (X3), dan Working Capital Turnover (X4) berpengaruh Positif dan Signifikan terhadap Harga Saham pada Perusahaan Sektor Jakarta Islamic Index yang terdaftar di Bursa Efek Indonesia Periode 2016-2019. Variabel yang berpengaruh dominan adalah Return On Equity (X3).